Srategi Guru Dalam Menanamkan Nilai -Nilai Akhlaq Siswa Di Madrasah Aliyah Nurul Ummah Sungai Duri Kalimantan Barat - Sholahuddin, Muhammad; Zakariyah, Zakariyah (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
This research aims to explore and analyze the strategies used by teachers in instilling moral values ??in students at Madrasah Aliyah Nurul Ummah Sungai Duri. A descriptive qualitative approach with case studies was used in this research to gain an in-depth understanding of the phenomenon under study. The research results show that the strategies used by teachers in instilling moral values ??in students are carried out through various methods, such as exemplary methods, habituation, and providing advice and motivation. The exemplary method is the main foundation, where teachers provide direct examples of daily activities at school. The habituation method is carried out through routine activities that contain religious values, such as congregational prayers, reading the Al-Qur'an/iqro, and praying together. Teachers also provide advice and motivation to remind them of the importance of carrying out worship, social etiquette, and motivating for the student's future. In implementing these strategies, there are supporting factors such as a good environment, adequate facilities and infrastructure, as well as awareness and willingness from teachers, parents and students. Meanwhile, inhibiting factors such as busy school activities, student laziness, lack of supervision from parents, as well as the influence of the environment and unfavorable relationships were also found